The use of the project-based learning methodology to improve oral expression in english - González Reina, Kristhel Del Cisne; Miñan Jirón, Lady Mishelle (Machala: Universidad Técnica de Machala, 2023)
This research focuses on the application of the Project Based Learning PBL methodology in the teaching-learning process. Regarding this, the improvement of Oral Expression in English in students in the ninth year of basic general education of parallel B, school year 2022-2023 is proposed. With the objective that students develop oral expression and improve fluency, clarity, and coherence in their message, also using body movements and gesticulation, a lesson system is implemented. This research work is guided by the quantitative paradigm with an experimental design that seeks to verify itself through hypotheses, understand the effect of the variables, and then analyze and measure them to obtain results. Likewise, observe the manifestation of the problem. First, a diagnostic test is carried out on the 27 students, which allows to adapt a system of lessons to improve the students' oral expression through appropriate topics, then compare the results of the diagnosis with the final project post-test obtaining as evidence that the students presented problems at the beginning due to the lack of vocabulary and the use of their mother tongue. However, if teachers focus on a skill oral expression and teach content according to what the student is going to use in an exercise in class, the oral performance will improve to a certain degree, which was verified with the Chi square. In conclusion, the use of the PBL teaching methodology improves oral expression through dynamic and entertaining lessons for students.
This research focuses on the application of the Project Based Learning PBL methodology in the teaching-learning process. Regarding this, the improvement of Oral Expression in English in students in the ninth year of basic general education of parallel B, school year 2022-2023 is proposed. With the objective that students develop oral expression and improve fluency, clarity, and coherence in their message, also using body movements and gesticulation, a lesson system is implemented. This research work is guided by the quantitative paradigm with an experimental design that seeks to verify itself through hypotheses, understand the effect of the variables, and then analyze and measure them to obtain results. Likewise, observe the manifestation of the problem. First, a diagnostic test is carried out on the 27 students, which allows to adapt a system of lessons to improve the students' oral expression through appropriate topics, then compare the results of the diagnosis with the final project post-test obtaining as evidence that the students presented problems at the beginning due to the lack of vocabulary and the use of their mother tongue. However, if teachers focus on a skill oral expression and teach content according to what the student is going to use in an exercise in class, the oral performance will improve to a certain degree, which was verified with the Chi square. In conclusion, the use of the PBL teaching methodology improves oral expression through dynamic and entertaining lessons for students.
Keywords: EXPRESSION; SYSTEM; LESSON; TEACHING-LEARNING